2008
DOI: 10.1007/s00330-008-0861-9
|View full text |Cite
|
Sign up to set email alerts
|

Contrast enhancement in multidetector-row computed tomography (MDCT) of the abdomen: intraindividual comparison of contrast media containing 300 mg versus 370 mg iodine per ml

Abstract: The purpose of this study was to intraindividually evaluate the difference in intraluminal vessel and parenchyma contrast enhancement of two different iodine concentrations in multidetector-row computed tomography (MDCT) of the abdomen. Eighty-three patients underwent baseline and follow-up MDCT-scanning (Somatom Sensation 16; Siemens, Forchheim, Germany) of the abdomen using contrast media containing 370 mg iodine/ml (protocol A; Ultravist 370, Bayer Schering Pharma, Berlin, Germany) and 300 mg iodine/ml (pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
1
11
1
Order By: Relevance
“…Our data are in accordance with those of previous investigations in patients with or without cirrhosis [23][24][25] and support the notion that the total amount of iodine, and not the iodine delivery rate, is a major determinant of vascular and parenchymal enhancement during the hepatic parenchymal phase [26].…”
Section: Effect Of Contrast Materials Iodine Concentrations During LIVsupporting
confidence: 93%
“…Our data are in accordance with those of previous investigations in patients with or without cirrhosis [23][24][25] and support the notion that the total amount of iodine, and not the iodine delivery rate, is a major determinant of vascular and parenchymal enhancement during the hepatic parenchymal phase [26].…”
Section: Effect Of Contrast Materials Iodine Concentrations During LIVsupporting
confidence: 93%
“…Tsurusaki et al and Furuta et al we then found that at least in venous phase ceCT images there were no differences between the two contrast media. This is in line with studies in dedicated MDCT in which IDR and iodine dose adapted injection protocols were used [21,22].…”
Section: Discussionmentioning
confidence: 76%
“…This in turn has a significant influence on contrast enhancement, as e.g. the IDR directly influences arterial enhancement whereas the total iodine dose applied exerts its main effect on contrast enhancement in the portal venous phase [19][20][21][22]. Therefore, these two parameters have to be kept constant between injection protocols in order to be able to compare contrast media with different iodine concentrations in different areas of the body.…”
Section: Discussionmentioning
confidence: 97%
“…A number of papers have evaluated the influence of different parameters for contrast administration, including iodine concentration, total volume of contrast, injection rate, and other factors [20, 2325], on arterial and/or parenchymal enhancement [13], but very limited general recommendations on optimised parameters could be gleaned from these publications. The very simple and basic relation, expressed as “the higher the iodine application per unit of time, the higher the enhancement” seems to be an established general rule for MDCT angiography following most of these publications [13, 19].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to some recently published papers [20], where patients were examined with different iodine concentrations but constant iodine flux rates, the injection protocol in the present study was not adapted to the iodine concentration of the agent used. In addition, the various centres participating in the present trial were to use their own injection protocols.…”
Section: Introductionmentioning
confidence: 99%